Circulating Tumor DNA and [18F]FDG-PET for Early Response Assessment in Patients with Advanced NSCLC - Heidi Ryssel; Lise Barlebo Ahlborn; Danijela Dejanovic; Sune Hoegild Keller; Mette Pøhl; Olga Østrup; Annika Loft; Barbara Malene Fischer; Seppo Wang Langer; Andreas Kjaer; Tine Nøhr Christensen (Diagnostics, 2025)
Background/Objectives: Identifying treatment failure at earlier time points to could spare cancer patients from ineffective treatment and side effects. In this study, circulating tumor DNA (ctDNA) and [18F]FDG-PET/CT were investigated during the first cycle of anticancer therapy in patients with advanced non-small cell lung cancer (NSCLC) to explore their potential for early response evaluation. Methods: Patients with advanced NSCLC receiving first-line therapy with immune checkpoint inhibitors and/or chemotherapy were included. CtDNA and [18F]FDG-PET/CT assessments were conducted before treatment and at weeks 1 and 3 during the first cycle of therapy. ctDNA quantification was performed using a targeted next-generation sequencing (NGS) panel, and the least favorable change in any mutated allele frequency at a given time was used for analysis. [18F]FDG-PET/CT was quantified using sumSULpeak and metabolic tumor volume (MTV4.0). Early changes in ctDNA levels and [18F]FDG-PET parameters were compared with final treatment response, measured by RECIST after 12 weeks, as well as progression-free survival and overall survival. Results: Of the sixteen included patients, eight were non-responders. ctDNA mutations were detected in baseline blood samples in eight patients. Changes in ctDNA level, MTV4.0, and sumSULpeak at week 3 indicated response in 7 out of 8 patients, 13 out of 15 patients, and 9 out of 15 patients, respectively. At week 3, no false increases were seen with ctDNA and MTV4.0. Conclusions: These results suggest that early changes in ctDNA and [18F]FDG-PET/CT at 3 weeks of treatment could be used to early assess treatment response. Increased levels of ctDNA and MTV4.0 at week 3 were only observed in patients with treatment failure.